Characterization of the Lytic Phage Flora With a Broad Host Range Against Multidrug-Resistant Escherichia coli and Evaluation of Its Efficacy Against E. coli Biofilm Formation - Jiang, Liming; Jiang, Yaxian; Liu, Wen; Zheng, Rui; Li, Chenghua (Frontiers in Veterinary Science, 2022)
Escherichia coli is a gram-negative bacterium that is distributed widely throughout the world; it is mainly found in contaminated food, the poultry industry and animal faeces. The emergence of antibiotic-resistant E. coli poses a threat to human and animal health, which has led to renewed interest in phage-based therapy. E. coli biofilm control and prevention are of great importance. In this study, the isolated phages Flora and KM18 were found to belong to the family Myoviridae; the optimal preservation buffer was pH=6 7, and the phage genome sizes were 168,909 (Flora) and 168903 (KM18) bp. Phage Flora had a broader lytic spectrum than KM18. Phage Flora had a better antibiofilm effect than kanamycin sulfate in high-concentration E. coli cultures. A combination of the phage Flora and kanamycin sulfate showed better antibiofilm effects than Flora or kanamycin sulfate alone in low-concentration E. coli cultures. These characteristics can serve as a guideline for the selection of effective candidates for phage therapy, in this case for antibiotic-resistant E. coli control in the poultry industry.